Neglected Tropical Protozoan Diseases: Drug Repositioning as a Rational Option - Sbaraglini, Maria Laura (2016)
Neglected tropical diseases represent a major sanitary problem and a huge economic burden to endemic countries, and are currently expanding to non-endemic countries owing to migration currents. Though long abandoned in the past, recent research on novel therapeutics has already started to show results. Drug repositioning is one of the prominent, more successful strategies to approach the development of new treatments for these diseases. Here we present an overview on the limitations of the current available medications to treat African trypanosomiasis, Chagas disease and Leishmaniasis, along with a review on drug candidates presently undergoing clinical trials and drug candidates identified through drug repositioning initiatives.